Parent Support Strategies: Final Report - Warrilow, Prue; Fisher, Karen; valentine, kylie (UNSW Sydney, 2004)
The Parent Support Project aimed to develop an understanding of the support and information needs of parents. In addition, the project aimed to develop, implement and evaluate systems to improve the coordination between existing parent support services within each local government area (LGA) in the Cumberland Prospect Families First Area (Auburn, Parramatta, Holroyd, Baulkham Hills and Blacktown) to increase the access families have to these services. In this report, parent support means services to assist parents with parenting. The project addresses the needs of families in the Cumberland Prospect Families First Area with children 0-8 years, particularly families with a parent or child with a disability, families from culturally and linguistically diverse (CALD) backgrounds and Aboriginal and Torres Strait Islander (ATSI) families.
SPRC Report 7/04